Evaluation of the let’s sports movement program in the ministry of youth and sports - Perdiyansa, Perdiyansa; Setiawan, Iwan; Wasan, Aan (Gladi : Jurnal Ilmu Keolahragaan, 2022)
Research in general aims to obtain information about the evaluation of community sports movements. The method used is evaluation research. In this study, the evaluation of the CIPP model program (Context, Input, Process, and Product) was used. The approach used in this study is cross-sectional, namely research in one period of time that only examines developments in certain stages. The questionnaire instrument was used to determine the factual conditions of the implementation of the Let's Sports Movement program, interview guidelines were used to find out in depth the findings obtained through questionnaires, the documentation study was used to study documents related to the implementation of the Let's Sports Movement program. The population in this study is West Java Dispora, Kab. Lebak Dispora and Tana Toraja Dispora. Evaluation analysis is carried out through the stages: collecting data, analyzing data, providing assessments and making decisions and making recommendations. The results showed that the Let's Sports Movement programs were well implemented. However, there are still a number of things that need to be addressed in order to be able to improve the management system for the Let's Sports Movement Program